Against rigid rules: Keynes's economic theory - Elke Muchlinski (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2003)
This paper provides textual evidence of Keynes's position on monetary policy and shaping international monetary relations. One result of my contribution is that the famous dichotomy rules versus discretion is of no relevance to his economic theory, because he used the term rules not in the meaning of a formal brilliantly designed notion.He definitely made a distinction between non-rigidly-fixed-rules and discretion. I give an explanation why his economic theory is not compatible with principles of constructivism, empiricism and ontological realism by referring to a key term of his economic writings, i.e., discretionary decision.
Keywords: B22; B4; E58; F33; 330; History of economic thought since 1925; Methodology; Central Banking; Inernational monetary arrangements and instititions